Pengaruh Kompetensi Guru Dan Kultur Sekolah Terhadap Kinerja Guru Sekolah Dasar Negeri Banjarharjo Kabupaten Brebes - Lina Maulina; Suci Suci (Jurnal IAI Bunga Bangsa Cirebon, 2022)
The quality of education tends to decrease as a result of the less than optimal performance of teachers in carrying out their duties, it is coupled with the lack of competence possessed by teachers, school culture that is not implemented properly. This study aims to determine and analyze the effect of teacher competence and school culture on teacher performance at SD Negeri in Banjarharjo, Brebes Regency. The approach used in this study is a quantitative approach with the type of method used in this study is a type of survey method with an associative quantitative approach with analytical techniques including normality test, homogeneity test, linearity test, partial regression test and multiple regression test. The results of the descriptive analysis show that the performance of teachers in elementary schools in Banjarharjo District, Brebes Regency is as follows: 4, 99% schools have very good performance; 29.1% of schools have good teacher performance; 41.6% medium category; 19.1% unfavorable category; and 5% of schools have a bad category. The results of hypothesis testing indicate that there is a positive and significant effect of teacher competence and school culture on teacher performance (Adjusted R2 = 0.155). This explains the competence of teachers and school culture together able to explain the variance of teacher performance by 15.5% Based on the data from the research and discussion, it can be seen that: 1) There is a positive and significant influence between teacher competence on teacher performance at SD Negeri Banjarharjo, Brebes Regency. 2) There is a positive and significant influence between school culture on the performance of SD Banjarharjo teachers, Brebes Regency. 3) There is a positive and significant influence between teacher competence and school culture together on the performance of teachers at SD Negeri Banjarharjo, Brebes Regency. Abstrak Kualitas pendidikan cenderung menurun yang di akibatkan dari kurang optimalnya kinerja guru dalam menjalankan tugas, hal itu ditambah dengan kurangnya kompetensi yang dimiliki oleh guru, budaya sekolah yang tidak dilaksanakan dengan baik. Penelitian ini bertujuan untuk mengetahui dan menganalisis pengaruh kompetensi guru dan kultur sekolah terhadap kinerja guru Sekolah Dasar Negeri Banjarharjo Kabupaten Brebes. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kuantitatif dengan jenis metode yang digunakan dalam penelitian ini adalah jenis metode survey pendekatan kuantitatif asosiatif dengan teknik analisis meliputi uji normalitas, uji homogenitas, uji linieritas, uji regresi parsial dan uji regresi ganda. Hasil analisis deskriptif menunjukkan bahwa kinerja guru di Sekolah Dasar Kecamatan Banjarharjo, Kabupaten Brebes adalah sebagai berikut: sebesar 4, 99% sekolah memiliki kinerja sangat baik; 29,1% sekolah memiliki kinerja guru yang baik; 41,6% kategori sedang; 19,1% kategori kurang baik; dan 5% sekolah memiliki kategori tidak baik. Hasil pengujian hipotesis menunjukkan bahwa terdapat pengaruh positif dan signifikan kompetensi guru dan kultur sekolah terhadap kinerja guru (Adjusted R2=0,155). Hal ini menjelaskan kompetensi guru dan kultur sekolah secara bersama-sama mampu menjelaskan varian kinerja guru sebesar 15,5%. Berdasarkan data hasil penelitian dan pembahasan maka dapat diketahui bahwa: 1) Terdapat pengaruh yang positif dan signifikan antara kompetensi guru terhadap kinerja guru Sekolah Dasar Negeri Banjarharjo Kabupaten Brebes. 2) Terdapat pengaruh yang positif dan signifikan antara kultur sekolah terhadap kinerja guru Sekolah Dasar Negeri Banjarharjo Kabupaten Brebes. 3) Terdapat pengaruh yang positif dan signifikan antara kompetensi guru dan kultur sekolah secara bersama-sama terhadap kinerja guru Sekolah Dasar Negeri Banjarharjo Kabupaten Brebes